Peran laktoferin susu kuda sebagai imunomodulator dalam respon imun humoral = the role of horse milk lactoferrin as immunomodulator in humoral immune response - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
ABSTRACT Lactoferrin is a multifunctional defense protein, eg. as immunomodulator , which is known as glycoprotein which has 80 kDa molecullar weight. The aim of this research is to characterize of horse milk lactoferrin as immunomodulator in humoral immune response. Lactoferrin in defiled horse milk, was isolated and purified on Ion Exchange (CM Sephadex C-50) and Gel Filtration (Sephadex G-75) column. Horse milk lactoferrin is administered orally into a group of 6-8 weeks old female Balb/c mice. The dose of lactoferrin were : 0 nig (control)